Leadership Development in the Context of a Russian Beneficiation Plant: Quasi-Experiment - Marina Kravtšuk (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of the study was to answer the research question: how to develop leadership in the context of a Russian beneficiation plant? A quasi-experiment using a pre-and post-intervention design was conducted by an immersed researcher, providing verifiable data, involving 3 levels of management, using MLQ as a tool for measurement with the specification of effectiveness criteria. Results of the study indicated that context-based leadership development allows for achieving statistically significant change in the leadership styles and effectiveness of the management, leadership styles of executives were mirrored by middle managers and supervisors. The contextualization and provided statistics allow for comparison with the other studies and enable improvement of the body of knowledge, providing guidance for future research and practice.